EFEKTIVITAS PENGGUNAAN E-PROCUREMENT DARI SUDUT PANDANG PENYEDIA PADA PT. JATIM PRASARANA UTAMA - Gina Nur Maya Jannah; Agus Widiyarta (Halu Oleo University, 2023)
In realizing good governance or good governance the government takes one step through e-procurement activities. PT Jatim Prasarana Utama as one of the BUMD companies also participates in making changes by participating through electronic procurement procedures. The study aims to understand and analyze whether the implementation of e-procurement that has been issued by the government can run effectively from the point of view of the provider of goods or services in its use. The research method used is descriptive qualitative research, in this study using three indicators of integration, purpose, and adaptation from Ducan's theory. The results obtained in this study indicate that the implementation of electronic-based goods or services procurement activities or e-procurement activities from the point of view of PT Jatim Prasarana Utama as a provider of goods or services can be said to be running effectively.